The Urban Heritage Tourism Development Strategies in Gajah Mada Denpasar Heritage Area Based on The Visitors’ Satisfaction - Tamaratika, Fenilia; Wiranatha, Agung Suryawan; Suryawardani, I Gusti Ayu Oka (E-Journal of Tourism; Volume 8 Number 2 (September 2021)DO - 10.24922/eot.v8i2.78276, 2021)
Market driven is one of the aspect of tourism development strategy approaches. The purpose of this research is intended to formulate development strategies for Gajah Mada Denpasar Heritage Area as an urban heritage tourism destination based on the level of visitors’ satisfaction. This research is based on descriptive quantitative method. The data used in this study are qualitative and quantitative data that obtained through literature study, observation, interviews and questionnaires to 100 respondents who had experienced on visiting Gajah Mada Heritage Area before the Covid-19 pandemic in Indonesia. Data were analyzed using Importance Performance Analysis (IPA) and supported by descriptive analysis methods. The results showed that the development strategy needs to be emphasized on intensify the bad performance of the tourism destination elements in quadrant I and maintain the good performance of the tourism destination elements which are the part of quadrant II, based on the Cartesian quadrant’s result.